(3HgLI GdeMGad hHZjI GdCeGKd aj JdNjU GdSjQ hGdCNdGb hGdTeGFds - (3CHh RcQjG jMji Hf CHj HcQ GdYGeQj,J (B893 (3g` s ((3CMeO Hf Gd UOjb Hf eMeO GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdHQ GdQMje hHYO aEf ef CLd eG jfHZi eYQaJg hJYQjag hJUfjag GdcdGe ai GdYdhe GdfHhjI s
(3BNQgG (B:s
(3bGd GdeDda cGf Gddg dg (B: (3hgPG EfJLR GdcdGe Ydi GdhLg GdPi TQWfGg gh MSHi hfYe Gdhcjd , hfYe Gdehdi hfYe GdfUjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTi GdfSNI HYV GdJYdjbGJs
(3HChdgG QhGjI GdcJGH Yf GdeUfa s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs